IMMUNOLOGICAL REACTIVITY AND PERIPHERAL BLOOD DNA-CYTOMETRY IN CHILDHOOD ONCOLOGICAL DISEASES - Z. R. Khamatdinova (SPb RAACI, 2014)
Distinct data concerning DNA cytometry of peripheral blood populations are relatively scarce, including oncopathological conditions. Among tasks of present work, we evaluated effects of malignancies upon functional state of peripheral blood cells and determination of correlations between cell ploidy, cell cycle kinetics and parameters of immune system.